Tourism skill development initiatives in three Southern African Development Community countries: A policy guide analysis - Rasethuntsa, Boitumelo Caroline (Turyzm/Tourism, 2022)
Tourism is a keystone of the Southern African Development Community economy. However, the region has failed to maintain a fair market share in the global tourism industry as the Travel and Tourism Competitive Index 2007 to 2019 shows. Human resources are regarded as one of the pillars that stimulate a competitive tourism industry, hence, it is critical for countries to formulate appropriate human resource development policies and plans to secure economic benefits from their tourism activities. The main aim of this study is to develop an understanding of the strategies that Southern African Development Community countries can adopt to develop tourism skills. To attain this objective, this study investigates the strategies adopted by Tanzania, Mauritius and Botswana with the aim of informing policies and paving the way for other countries to improve tourism skills for the collective effectiveness of the entire region. Through a secondary research method, a comprehensive literature review was conducted to explore the tourism skill development strategies utilised by three regional countries so that less competitive peers can draw lessons for policy improvement and reform. This study shows that investment in tourism education, engaging international professionals, collaboration among stakeholders, and placing tourism human resource development as a national strategic area, are critical.